Analisis Penerapan Design Thinking dalam Strategi Diversifikasi Produk Teh Serenitea pada Usaha Mikro Hexa Corp Indonesia - Devina Ratnaningtyas Kristy Alimin; Trisna Insan Noor (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
The rapid growth of small and micro-scale beverage industries in Indonesia has positioned the herbal tea sector as a promising yet challenging field. However, herbal tea is currently less favored by the younger generation due to challenges in taste acceptance. To address this issue, HEXA CORP introduced product innovation through its Serenitea brand. Nevertheless, despite this innovation, sales volume declined by 32% between November 2024 and January 2025, while profit realization reached only 45% of the target, resulting in a negative deviation of 55%. The low consumer acceptance of herbal tea flavor innovation, particularly among the younger generation, became the main factor. This study applies the Design Thinking approach to explore product diversification opportunities and evaluate their impact on business profitability. The research was conducted at HEXA CORP’s business location in Jatinangor from February to June 2025 using a descriptive qualitative design guided by Design Thinking principles. The analysis revealed consumer journey issues at the onboarding, retention, and purchasing stages, primarily related to pricing and product attributes. Through ideation and prototyping, HEXA CORP developed affordable single-use herbal tea variants with improved flavors and packaging. Market testing identified middle-income students as the key consumer segment, with sales increasing by 71.43% and profitability rising by 11.51%. The resulting diversification strategy focused on packaging enhancement, product legality and certification, discount programs, and targeted marketing. These findings highlight the positive impact of product diversification on HEXA CORP’s business performance.